Rises in antibody to enteric gram negative bacilli after open heart surgery: a possible mechanism for postoperative pyrexia. Issue 7 (July 1985) - Freeman, R; Gould, F K
Abstract : Paired sera, taken before operation and 10-14 days after operation from 64 patients having open heart surgery and 10 having closed heart surgery, were examined for agglutinins to seven common serotypes of Escherichia coli. The results showed that, while 20% of both groups of patients had detectable agglutinins before operation, new antibodies appeared after operation in 69% of patients having open heart surgery compared with only 10% of those having closed heart surgery, a significant difference. Thirty six pairs of sera were also examined for the preoperative presence and postoperative development of antiendotoxin. Of 22 open heart patients shown not to possess antiendotoxin before operation, 18 showed the antibody after operation, whereas none of the eight seronegative patients acquired the antibody after closed heart surgery-again a highly significant difference. These results are consistent with the hypothesis that endotoxin and other products of enteric Gram negative bacilli circulate shortly after cardiopulmonary bypass, possibly arising directly from the gut and perhaps explaining the pyrexia seen commonly at this time.